A rendezvous point‐based data gathering in underwater wireless sensor networks for monitoring applications. (8th January 2022) - Choudhary, Monika; Goyal, Nitin
Summary: In underwater wireless sensor networks (UWSNs), most of the mobile sink data gathering scheme assumes that sensor nodes are static. Also, very limited set of works aim to eliminate the data redundancy during data gathering. Moreover, the data collection latency, error rate and load have to be considered in addition to the buffer space and energy level of the nodes. Here, a mobile sink data gathering technique is designed where rendezvous points (RPs) and sojourn times are selected. The RPs, where the mobile sinks stop to gather the data, are selected based on the node density, current traffic load and energy level of nodes. The proposed scheme, that is, adaptive distributed mobile sink data gathering (ADMSDG), eliminates data redundancy even by considering mobility of all the nodes including sink node. Here, multihop data gathering is also considered to address the energy hole problem near the sink based on similarity index. To examine the result, proposed scheme and other state‐of‐the‐art schemes are implemented in NS2.30 having the same environment. Obtained results show that when proposed scheme is experimented with respect to number of nodes, the proposed ADMSDG technique achieves 18% high data collection accuracy with 5% reduced data collection delay and 5% less energy consumption. Similarly, when proposed scheme is experimented with respect to transmission range, the proposed ADMSDG technique achieves 18% high data collection accuracy with 12% reduced data collection delay and 8% less energy consumption. Abstract : The proposed data gathering technique reduces data collection latency, error rate and load in addition to the buffer space and energy consumption using rendezvous points (where mobile sinks stop to gather the data). The decision for a node to act as a RP will be based on the high dense zone. If any node N i comes in direct transmission range of MS, it receives the beacon and sends a reply to the MS. Otherwise, N i transmits the data to its nearest CN such that the CNs forward the collected data to the moving MS.